2019
DOI: 10.1097/bpb.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

Increased acute postoperative wound problems following spinal fusion in overweight patients with adolescent idiopathic scoliosis

Abstract: This study assessed the rate of adverse wound events in individuals with adolescent idiopathic scoliosis who underwent a posterior spinal fusion and sought to determine if obesity was related to the rate of adverse wound events. A retrospective review of patients with adolescent idiopathic scoliosis that underwent posterior spinal fusion between 2001 and 2013 was performed. Preoperative, perioperative, and postoperative data, including wound adverse events, were obtained through medical record review. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The overall rates of superficial and deep infection rates were 2.4% and 1.7%, respectively. These fall within the ranges of previously reported rates,4,7–10,13 although the ranges vary widely. Similar investigations have shown an association between obesity and postoperative infection rate for patients with AIS undergoing PSF.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The overall rates of superficial and deep infection rates were 2.4% and 1.7%, respectively. These fall within the ranges of previously reported rates,4,7–10,13 although the ranges vary widely. Similar investigations have shown an association between obesity and postoperative infection rate for patients with AIS undergoing PSF.…”
Section: Discussionsupporting
confidence: 89%
“…The current consensus in the literature is also unclear, as some authors have demonstrated significant associations between obesity and EBL, 5,6 while others have not. 7,13,14 There are a number of limitations to this study. First, due to its retrospective and multicenter nature, there is an inherent potential for selection and reporting bias, leading to potential inconsistency in how outcome variables are reported, including SSIs in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While outcomes are reported to be satisfactory and often comparable among obese and nonobese patients treated with surgery when needed, peri-operative complications rate seems to be higher in most of the analyzed papers with few exceptions ( Table 3 ). 60 , 62 , 63 , 65 , 66 , 70 , 73 , 77 , 78 , 80 , 82 , 86 , 88 , 90 , 92 - 94 , 97 , 101 , 102 , 105 , 107 , 109 - 112 , 114 , 116 , 118 , 123 , 125 , 126 , 129 , 131 , 133 , 135 , 139 - 141 , 146 - 148 , 151 - 153 , 166 -...…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity is an epidemic in the USA, with many downstream effects on the musculoskeletal system. For patients with adolescent idiopathic scoliosis (AIS), the recent literature has revealed that obese children may have larger curves on initial presentation [1][2][3][4], may fail brace treatment more often [1,5], experience longer operative times for surgical treatment of their spine deformities, and suffer from a higher rate of surgical site infections [4,6,7].…”
Section: Introductionmentioning
confidence: 99%